1992
DOI: 10.1111/j.1365-2141.1992.tb04566.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of several second generation serological assays to determine the true prevalence of hepatitis C virus infection in haemophiliacs treated with non‐virus inactivated factor VIII and IX concentrates

Abstract: To investigate the prevalence of hepatitis C virus infection in two risk groups, stored serum samples from treated haemophiliacs and intravenous drug users were tested for anti-HCV by both anti-C-100 based and second generation ELISAs (Abbott and Ortho) followed by testing in two confirmatory immunoblot assays that incorporate core as well as other non-structural antigens (Innogenetics LIA and Chiron RIBA-HCV test). Clear evidence of HCV infection was found in all but one of 78 haemophiliacs treated with non-v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
52
0
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(54 citation statements)
references
References 15 publications
1
52
0
1
Order By: Relevance
“…Among samples that tested positive both in the UBI EIA or Axsym-MEIA and in the immunoblot test or LIA (n ϭ 11), antibody reactivities to the core antigen were found to be the highest, as has been reported previously (6,9). NS5 antigen lines were the next highest in intensity.…”
supporting
confidence: 51%
“…Among samples that tested positive both in the UBI EIA or Axsym-MEIA and in the immunoblot test or LIA (n ϭ 11), antibody reactivities to the core antigen were found to be the highest, as has been reported previously (6,9). NS5 antigen lines were the next highest in intensity.…”
supporting
confidence: 51%
“…We have previously shown that infection with HCV variants other than type 1 (whose sequences are used for the antigens used in screening assays) may elicit an antibody response that is not cross-reactive with the NS-4-encoded antigens used in first generation screening assays (5-1-1, c100-3; McOmish et al, 1993). There is now substantial data showing the increased sensitivity of second generation serological assays that include the well conserved core protein in addition to non-structural proteins (Craxi et al, 1991 ;van der Poel et al, 1990van der Poel et al, , 1992Chan et al, 1991 ;Watson et al, 1992;Lelie et al, 1992), and it can be reasonably anticipated that such tests will be more effective than the original anti-C100-based assays for prevention of transfusiontransmitted HCV infection. Nevertheless, the serological response to HCV-encoded antigens is often narrow in specificity and is generally of extremely low titre.…”
Section: Analysis Of the More Variable Coding Regions Of The Viralmentioning
confidence: 99%
“…Acute infection with HC¥ following transfusion of infectious blood or blood products may fail to elicit antibody for several months Alter et al, 1989;van der Poel et al, 1992). Furthermore, individuals who are only marginally immunosuppressed (such as renal dialysis patients, the elderly, haemophiliacs and neonates) generally show very restricted and idiosyncratic patterns of serological reactivity, often to only one (or possibly none) of the four antigens used in current screening assays Watson et al, 1992;Allain et al, 1991;Lam et al, 1993).…”
Section: Analysis Of the More Variable Coding Regions Of The Viralmentioning
confidence: 99%
“…Hepatitis C was isolated in 1989 and is now known to be the major cause of non-A non-B hepatitis Kuo et al, 1989). It is now estimated that the majority of those who received non-virusinactivated factor concentrate became hepatitis C positive (Watson et al, 1992).…”
mentioning
confidence: 99%